Analysis of Curriculum Implementation In Elementary School - Adi Prehanto; Asep Nuyadin (Universitas Pendidikan Indonesia (UPI), 2022)
Curriculum is a set of systems consisting of planning, process or implementation, and evaluation dimensions. Awareness of the importance of the curriculum as an integral part of education requires education stakeholders, especially teachers, to always innovate and develop good learning. Curriculum issues are closely related to how the process or implementation of the curriculum is carried out in educational units. This research raises the topic of the quality of curriculum implementation in elementary schools. The purpose of this study is to analyze the implementation of the curriculum in elementary schools. This research applied descriptive quantitative. The data collection technique used a questionnaire, which was distributed to elementary school teachers in Indonesia. The number of samples in this study were 290 respondents carried out randomly. Respondents consisted of elementary school teachers from low to high levels throughout Indonesia. The results of this study are that the average implementation of the curriculum that is carried out is still not maximally carried out, both in planning, process and evaluation. This research has implications for fulfilling the quality of curriculum implementation which must be carried out optimally, so that the expected educational goals or curriculum can be achieved. The results of this study are that the average implementation of the curriculum that is carried out is still not maximally carried out, both in planning, process and evaluation.